Prevalence of Dental Caries and Oral Health Practices Among Preschool Children: School Screening Programs in Benghazi City, Libya - Hawwa Beaayou,; Khawlah Shawash,; Fatimah Aebeedah,; Mahmoud Elsharif, (AlQalam Journal of Medical and Applied Sciences, 2025)
Dental caries is a common chronic disease in children, with significant effects on oral health, nutrition, and overall quality of life. Despite being preventable, untreated caries in preschool-aged children remains a global and regional public health concern, particularly in developing countries. Therefore, this study aims to assess the prevalence of dental caries and oral health practices among preschool children in Benghazi City, Libya, and to provide baseline data for school-based oral health screening and preventive programs. A descriptive cross-sectional study was conducted among 350 preschool children aged 3–5 years, recruited from five administrative areas in Benghazi. Data collection included a validated questionnaire addressing sociodemographic information, oral hygiene behaviors, dietary habits, and dental visits. Clinical examinations were conducted using the WHO criteria to assess the DMFT index. Statistical analysis was performed using SPSS version 28. Chi-square, t-test, Mann–Whitney, and Kruskal–Wallis tests were used. A p-value ≤ 0.05 was considered statistically significant. The mean dmft score was 1.91 ± 2.55, with 56.9% of children experiencing dental caries and 43.1% being caries-free. Oral health practices showed that 83.7% of children brushed under parental supervision; however, only 53.8% brushed twice daily. Additionally, 74.9% reported daily consumption of sugary foods. Significant associations were found between DMFT scores and tooth brushing frequency, while no significant differences were observed with sociodemographic variables. The prevalence of dental caries among preschool children was high. Whereas oral health practices, especially tooth brushing frequency and sugar intake, were significantly linked to caries experience. Targeted preventive programs and parental education are urgently recommended to improve oral health in this vulnerable population.